Two-phase operational maps, pressure drop, and heat transfer for flow boiling of R236fa in a micro-pin fin evaporator. (April 2017) - Falsetti, C.; Jafarpoorchekab, H.; Magnini, M.; Borhani, N.; Thome, J.R.
Highlights: Two-phase flow boiling in a micro-pin fins evaporator is experimentally investigated. Local fluid temperature and 3D heat conduction are implemented in the data reduction. Inlet restrictions improve flow stability at low mass flux values. Heat transfer performance is strongly dependent on vapor quality, mass flux and heat flux. Flow patterns have an essential impact on heat transfer coefficient trends and magnitudes. Abstract: Cooling the new generation of 3D high power electronic chips is one of the leading challenges in microelectronics, as it is a key to achieve high computational performance at lower cooling system power consumption, thus reducing the operating cost. Two-phase flow boiling in two micro-pin fin heat sinks is studied here for this cooling process. Each micro-evaporator has a heated area of 1 cm 2 and contains 66 rows of cylindrical micro-pin fins with an in-line configuration and diameter, height and pitch of respectively 50 μ m, 100 μ m and 91.7 μ m . The fluid tested is refrigerant R236fa. Channel entrances with and without inlet restrictions are tested in order to evaluate their relative effect on the stability of the flow. The inlet restrictions consist of an extra row of micro-pin fins with a larger diameter of 100 μ m placed at the inlet of the heated area. The present study investigates operational stable and unstable flow regimes, pressure drop and heat transfer performance for the two micro-evaporators (one with and one without inlet restrictions) by coupling high speed visualization of the micro-pin fins flow area with fine resolution infrared temperature measurements of the micro-evaporator base, which yields a 2D map of local heat transfer coefficients of the whole heated area. Working conditions tested have mass flux varying from 500 kg m −2  s −1 to 2500 kg m −2  s −1, heat flux ranging from 20 W cm −2 to 48 W cm −2, and a constant outlet saturation temperature of 30.5 °C. In agreement with previous studies for multi-microchannel evaporators, it is here observed that inlet restrictions extend the map of stable operational regimes, in particular toward lower values of the mass flux, without any appreciable increase of the pressure drop. Unlike evaporation through parallel microchannels, the heat transfer coefficient trends and magnitudes vary dramatically with the flow conditions (mass flux and heat flux), thus suggesting that micro-pin fins have a strong impact on the two-phase flow pattern development, in particular delaying the transition to annular flow.